Sound Alternation in the Speech of Georcians Living Turkey - Chokharadze, Vardo (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
Georgian characteristic phonetic changes are very frequent in the words borrowed from Turkish language, by which the loan word submits to Georgian pronunciation. Literary Turkish consonant “k” gives “kh” (ყ) in the words originated basically from Persian and Arabic languages. “Khalem” (Ar. Kalem - ქალემ) – “pen”. “Khalemi mome davtserona” (Im.); “Kurshunkhalemi gaquan?” (Ust.); “Khalemi ar gaq kai, aurufali khalemi kaia” (In); (N. Marr thought that Kalami is Georgian).